2010
DOI: 10.1167/10.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Holistic perception of individual faces in the right middle fusiform gyrus as evidenced by the composite face illusion

Abstract: The perception of a facial feature (e.g., the eyes) is influenced by the position and identity of other features (e.g., the mouth) supporting an integrated, or holistic, representation of individual faces in the human brain. Here we used an event-related adaptation paradigm in functional magnetic resonance imaging (fMRI) to clarify the regions representing faces holistically across the whole brain. In each trial, observers performed the same/different task on top halves (aligned or misaligned) of two faces pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(55 citation statements)
references
References 84 publications
12
42
0
Order By: Relevance
“…Neuroimaging studies in healthy controls reliably report greater activation in the fusiform gyrus during "intact" holistic face processing conditions, and conversely show decreased fusiform activation during conditions that disrupt the gestalt percept (Kanwisher and Yovel 2006). Additionally, studies have found that patients with focal lesions to the fusiform gyrus typically do not show the task effect, providing further evidence that the fusiform gyrus is critical to the gestalt processing of faces (Busigny et al 2010;Busigny et al 2014;Schiltz et al 2010). …”
Section: Discussionmentioning
confidence: 97%
“…Neuroimaging studies in healthy controls reliably report greater activation in the fusiform gyrus during "intact" holistic face processing conditions, and conversely show decreased fusiform activation during conditions that disrupt the gestalt percept (Kanwisher and Yovel 2006). Additionally, studies have found that patients with focal lesions to the fusiform gyrus typically do not show the task effect, providing further evidence that the fusiform gyrus is critical to the gestalt processing of faces (Busigny et al 2010;Busigny et al 2014;Schiltz et al 2010). …”
Section: Discussionmentioning
confidence: 97%
“…For example fMRI has shown release from adaptation based on the composite face illusion in visual areas selective to faces in the ventral stream (Schiltz & Rossion, 2006;Andrews et al, 2010;Schiltz et al, 2010). Since these effects arise even with completely incidental tasks (such as detecting a red dot superimposed on some stimuli) in regions considered to be primarily 'visual' in nature, it seems unlikely that decision processes play a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the OFA and FFA, which are primarily involved in recognition of individual identity (Grill-Spector et al, 2004), are sensitive to different aspects of faces (Liu et al, 2010). The OFA is sensitive to the presence of face parts (Pitcher et al, 2007;Harris and Aguirre, 2008;Andrews et al, 2010), whereas the FFA is preferentially involved in analyzing the configuration among them (Barton et al, 2002;Yovel and Kanwisher, 2004;Schiltz and Rossion, 2006;Rotshtein et al, 2007;Schiltz et al, 2010). Further, typical face processing requires the interaction of the OFA and FFA, because the FFA, for example, can be preserved in an individual with a lesion to the OFA and suffering from prosopagnosia (i.e., severe deficits in face recognition) (Rossion et al, 2003;Steeves et al, 2006).…”
Section: Discussionmentioning
confidence: 99%